Rapid Disease Progression in Human Immunodeficiency Virus Type 1—Infected Individuals with Adverse Reactions to Trimethoprim-Sulfamethoxazole Prophylaxis - Veenstra, Jan; Veugelers, Paul J.; Keet, Ireneus P. M.; van der Ven, Andre J. A. M.; Miedema, Frank; Lange, Joep M. A.; Coutinho, Roel A. (Clinical infectious diseases, 1997)
We studied the relation between the occurrence of adverse reactions to trimethoprim-sulfamethoxazole (TMP-SMZ) prophylaxis and the subsequent course of human immunodeficiency virus (HIV) infection in a cohort of homosexual men. Adverse reactions to TMP-SMZ were associated with a more rapid progression to AIDS (P < .001) and death (P < .001) and with a more rapid decline in CD4+ cell counts (P = .001). The median time to progression to AIDS was 14.9 months in subjects with adverse reactions to TMP-SMZ and 32.5 months in those without adverse reactions. After exclusion of Pneumocystis carinii pneumonia (PCP) and toxoplasmosis from the case definition of AIDS, the differences in the rate of progression to AIDS between subjects with and without adverse reactions to TMP-SMZ were still highly significant (P = .004). A low CD4+ cell count at baseline and the use of antiretroviral agents before the start of prophylaxis were predictors of adverse reactions to TMP-SMZ but did not account for the difference in progression to AIDS between subjects with and without adverse reactions to TMP-SMZ. In a univariate analysis, the relative hazard of adverse reactions to TMP-SMZ for progression to AIDS was 2.54 (95% confidence interval [CI], 1.50–4.28); in a multivariate analysis, it was 2.21 (95% CI, 1.29–3.81). The relative hazards of adverse reactions to TMP-SMZ for progression to AIDS with the exclusion of PCP and toxoplasmosis, CD4+ cell counts of <50/mm3, and death were 2.16 (95% CI, 1.25–3.72), 2.37 (95% CI, 1.36–34.12), and 3.21 (95% CI, 1.80–5.72), respectively. It is unclear whether adverse reactions to TMP-SMZ induce or merely predict progression of HIV disease.